Running economy, mechanics, and marathon racing shoes - Hunter, I.; McLeod, A.; Valentine, D.; Low, T.; Ward, J.; Hager, R. (Journal of Sports Sciences, 2019)
The choice of marathon racing shoes can greatly affect performance. The purpose of this study is to metabolically and mechanically compare the consumer version of the Nike Vaporfly 4% shoe to two other popular marathon shoes, and determine differences in running economy. Nineteen subjects performed two 5-minute trials at 4.44m/s wearing the Adidas Adios Boost (AB), Nike Zoom Streak (ZS), and Nike Vaporfly 4% (VP) in random order. Oxygen uptake was recorded during minutes 3-5 and averaged across both shoe trials. On a second day, subjects wore reflective markers, and performed a 3-minute trial in each shoe. Motion and force data were collected over the final 30 seconds of each trial. VP oxygen uptake was 2.8% and 1.9% lower than the AB and ZS. Stride length, plantar flexion velocity, and center of mass vertical oscillation were significantly different in the VP. The percent benefit of the VP over AB shoe was predicted by subject ground time. These results indicate that use of the VP shoe results in improved running economy, partially due to differences in running mechanics. Subject variation in running economy improvement is only partially explained by variation in ground time.